The role of the Kec. Religious Affairs Office Medan Tembung in an Effort to Reduce Early Marriage Rates - Ismet Sari; Fadhilla Alfitri; Sri Putri Rezeki; Putri Bungsu; Al Imran Winarva (Penerbit Jurnal Indonesia, 2022)
Central Java's high maternal mortality rate (MMR) reflects the risks faced by mothers during pregnancy and after childbirth. Child marriage in women is associated with early pregnancies, which are high-risk pregnancies. One of the leading causes of maternal mortality is complications during pregnancy, childbirth and childbirth. Empowerment is achieved through reproductive health counseling, one strategy for improving maternal self-care knowledge and behavior during pregnancy and postpartum. However, research on this topic is still very limited. One of the sub-districts in Central Java with higher child marriage rates than the national average is Tretepe district in Temanggung province. Therefore, researchers are interested in research in this area. The aim was to examine whether empowerment through better reproductive education really makes a difference in terms of self-care knowledge and behavior during pregnancy and after childbirth. It was conducted in a one-time case intervention group with The research headquarters is located in Tretepe District, Temangun Province. Methods The study was conducted using a quantitative approach. H. A preliminary experiment was conducted to compare the knowledge and behavior of the groups before and after the intervention. The learning approach is participatory learning where vulnerable groups are at the center of learning. Analytical techniques were performed through secondary data reviews, focus group observations, semi-structured interviews, and focus group discussions. Target communities (vulnerable youth groups) facilitate the identification of problems occurring in the area. That is, the region has a high rate of child marriage, followed by high early childhood maternal mortality (maternal mortality). Target groups are therefore encouraged to explore their potential as younger generations to educate mothers about healthy reproduction and self-care during and after pregnancy. As such, the research results will help find effective ways to reduce maternal mortality.